Transformation of wayang kulit performance from phsycal space to digital space - Sri Rochana Widyastutieningrum (Proceeding of International Conference on Art, Media, and Culture (ICAMAC), 2024)
Wayang Kulit (shadow puppet) performances have undergone a transformation from traditional performances straight into a digital show. Shadow puppet masterminds perform hybrid shadow puppet shows, by performing them live in front of the public, and also showing them online via YouTube, Instagram, and Tik Tok channels. The research reveals changes or transformations in wayang kulit performances. The research uses qualitative methods, with a phenomenological approach, using descriptive analysis techniques. The research uses data collection techniques through observation, literature study, and interviews. The results of the research show that shadow puppet performances have experienced changes in their form and performance space. More people watch shadow puppet shows on YouTube than people who see live performances. Shadow puppet shows prioritize entertainment, jokes, and humor as well as the presence of guest stars, rather than stories and messages, and noble values. Shadow puppet performances have experienced encouraging developments from the audience aspect, especially virtual performances. However, there has been a change or distortion of the values attached to the wayang kulit performances.